PENGARUH MOTIVASI PELAYANAN PUBLIK TERHADAP KEPUASAN KERJA PEGAWAI PADA LAPAS KELAS IIA KEROBOKAN - Putra, Kadek Heri Dharmawan; Pangestuti, Naniek (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This study aims to determine the effect of public service motivation on employee job satisfaction at Kerobokan Class IIA Correctional Institution. This study uses quantitative research methods with purposive sampling techniques for as many as 43 employees. The data was collected using a questionnaire distributed via Google Forms, and 33 statements were used as indicators in the study. The data analysis technique carried out is through the normality test, simple linear regression test, significance test, and determination test which is processed using IBM SPSS software version 27. The results showed an influence of public service motivation on job satisfaction. The results of the determination test obtained by the public service motivation variable provide an influence of 58.3% on the job satisfaction variable, while other variables influence the remaining 41.7%. It can be concluded that there is a relationship between public service motivation and job satisfaction at Kerobokan Class IIA Correctional Institution. Keywords: Public Service Motivation; Job Satisfaction; Correctional Institution